Barriers and facilitators to perceived diabetes self-management in Arab American patients with diabetes. Issue 3 (June 2020) - El Masri, Dana; Koscielniak, Nikolas; Piatt, Gretchen; DiZazzo-Miller, Rosanne; Arnetz, Judith; Jaber, Linda A.
Highlights: A survey was used to understand the impact of culture on diabetes-self management. Multiple factors dictate Arab American's perception of diabetes self-management. It's important to integrate cultural influences into diabetes self-management. Abstract: Aims: To assess perceptions surrounding diabetes self-management (DSM) behaviors in Arab American patients with diabetes. Methods: A 39-item survey was constructed from focus group discussions designed to better understand the impact of Arab American culture on DSM behaviors. The survey assessed perceptions about diet, adherence to medications, exercise, healthy lifestyle, and family support. Results: Two hundred Arab Americans with diabetes completed the survey via face-to-face interviews. Most patients were female (59%), over fifty years of age (79%), and immigrated from Lebanon (73%). Receiving instructions in Arabic, having family support, family understanding of food choices, and employment status were found to be important predictors of the perceived importance of DSM. Conclusions: Our findings suggest that there are multiple factors that dictate Arab American's perception of the importance of DSM. The survey that was constructed may serve as a valuable tool for providers to assess DSM perceptions in order to provide patient-centered care that will help to improve diabetes outcomes. This study supports the importance of integrating cultural influences into DSM education and support when providing care to a population with a strong cultural identity.